Formation of cloud-based learning environment for professional training in programming - N. A. Kharadzjan (Academy of Cognitive and Natural Sciences, 2014)
The article is devoted the question of forming a full functional based on cloud technology to study subjects from programming cycle for specialists in programming. The object of the research - the process applying cloud technologies in learning. The subject of the research - cloud technology in training of specialists in programming. The purpose of the research - forming a full functional learning environment for training of specialists in programming based on cloud technology. The method of research - analyses. To achieve the goal of the research was conducted review of existing integrated programming environments. First of all, such environments should be based on cloud technologies, since among the services provided by cloud technologies is a service SaaS. Also, the environment should support the possibility of developing programs in different programming languages, which allowed organize learning on programming in a single environment. In this environment was chosen cloud environments Cloud9 IDE. Cloud9 IDE is an Internet environment for development applications in programming language Javascript for Node.js, HTML5/CSS, PHP, Java, Ruby on Rails, C/C++, Python, allowing you to work in free and paid modes. Since service SaaS used to provide learning process and research only specialized software, therefore necessary to provide the learning materials (texts of lectures, laboratory and practical work, tutorials, self-study materials, etc.). These materials every student can study to self-pace, on their own trajectory. That student will acquire the ability and skills as needed - out bulky projects and approaches to learning.